1983
DOI: 10.1107/s0108767383001464
|View full text |Cite
|
Sign up to set email alerts
|

Space-group frequencies for organic compounds

Abstract: The space-group frequency for approximately 30 000 organic compounds in the NBS Crystal Data Identification File has been calculated for each of the 230 space groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 2 publications
3
58
0
Order By: Relevance
“…The distribution is shown in (Table 2). As observed earlier (Mighell, Himes & Rodgers, 1983), about 78% of the compounds were described in only five space groups. The distribution of compounds among the seven crystal systems (Table 3) shows that, for those structures with more than one formula unit in the asymmetric unit, there is about a 1-8-fold increase in the population of the triclinic system, whereas in the orthorhombic system the population decreased by about 1.5-fold when compared with the distribution for all crystal structures listed in the database.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The distribution is shown in (Table 2). As observed earlier (Mighell, Himes & Rodgers, 1983), about 78% of the compounds were described in only five space groups. The distribution of compounds among the seven crystal systems (Table 3) shows that, for those structures with more than one formula unit in the asymmetric unit, there is about a 1-8-fold increase in the population of the triclinic system, whereas in the orthorhombic system the population decreased by about 1.5-fold when compared with the distribution for all crystal structures listed in the database.…”
mentioning
confidence: 57%
“…These errors are due to compounds reported in (1) incorrect space group but correct crystal system, (2) incorrect space group and incorrect crystal system (Mighell, Himes & Rodgers, 1983). The unequivocal space-group determination of the given crystal structure can only be through the least-squares refinement of the structure in various candidate space groups and distinguishing between them through significance tests (Hamilton, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Kitaigorodsky's hypothesis has been verified experimentally. Of 29059 organic compounds whose crystal structures were determined prior to 1981, 75% crystallized in only five space groups (Mighell, Himes & Rodgers, 1983). These five space groups exhibit combinations of inversion centers, screw axes and/or glide planes which facilitate close-packing in all three lattice directions.…”
Section: Methodsmentioning
confidence: 99%
“…(viii) It has been observed that some space group symmetries are much more common than others in crystals formed from small organic molecules [16,17,18]. Inorganic systems show different space group frequencies [19,20].…”
Section: Potential Energy Surfaces and The Global Searching Problemmentioning
confidence: 99%